Controllable regulation of emulsion stability by a pH-responsive zwitterionic/anionic surfactant system. (15th March 2022) - Wu, Hairong; Chen, Xin; Tan, Rong; Luo, Yinglin; Hu, Yu; Li, Yingcheng; Hou, Jirui; Kang, Wanli
Highlights: A pH-responsive emulsifier composed of SDS and EAB was proposed. The interaction strength between SDS and EAB could be adjusted by regulation of pH. The emulsions stabilized by SDS and EAB could demulsify once 0.1M HCl was added. Abstract: In order to improve the recovery of crude oil and realize rapid demulsification of produced fluid, a pH-responsive zwitterionic/anionic surfactant system was proposed. The pH-responsive zwitterionic/anionic surfactant system consists of zwitterionic surfactant EAB (erucic amide carboxylic betaine) and anionic surfactant SDS (sodium dodecyl sulfate). By adjusting the pH value, the protonation degree of EAB could be controlled. Accordingly, the interaction between surfactants in the mixed system could be strengthened or weakened in neutral environment (pH = 6–8) or acidic conditions (pH = 2–4), respectively. In consequence, transformation between the emulsification and demulsification states for the emulsions stabilized by zwitterionic/anionic surfactant system could be effectively controlled by variation of the pH values. Meanwhile, the interfacial tension, average droplet size, microstructure and stability analysis of the mixed system emulsifying at various pH values were studied. For the emulsion stabilized by the pH-responsive zwitterionic/anionic surfactant system, the droplets size was evenly distributed and the average particle size was the lowest when the molar ratio of EAB to SDS was 4:6, whilst the average particle size increased significantly once the pH value was reduced down to 2 or 3. Above all, this study provides a new approach for the development of chemical flooding agents for enhancing oil recovery.